Prevalence of Oral Lesions Biopsies Among Different Laboratories - Layla Muhamad (Erbil Dental Journal)
Background: The oral cavity and jaws can be a host of multiple pathological lesions, which could be tumors, reactionary lesions, or cystic lesions.